Comparative transcriptome analysis reveals molecular mechanisms of resistance in Chinese cabbage to Plasmodiophora brassicae pathotype 11 - Qiu, Yue; Zhang, Jinhao; Deng, Chunju; Yuan, Jiasheng; Wang, Bowen; Meng, Han; Mohany, Mohamed; Zeng, Liting; Wei, Lanfang; Ahmed, Waqar; Ji, Guanghai (Frontiers in Microbiology, 2025)
Background and aimsClubroot caused by the soilborne obligate parasite Plasmodiophora brassicae, is a devastating disease of Chinese cabbage and other crucifers. The innate diversity and adaptability of this pathogen pose significant challenges to effective control measures. However, the varied response mechanisms exhibited by hosts to pathotype 11 at a molecular level are still unclear.Methods and resultsThis study investigated the resistance response and underlying molecular mechanism of two Chinese cabbage (Brassica rapa) varieties (JP and 83-1) to P. brassicae pathotype 11 through comparative transcriptome analysis and microscopic study. Results demonstrated that 14 days after inoculation (dai) is a critical time point of the infection process for resistant variety to inhibit the proliferation of P. brassica. Although the highly resistant variety JP did not exhibit a complete immune response to pathotype 11, it demonstrated a significant resistance level against P. brassicae pathotype 11 by restricting its proliferation in the xylem vessels. Microscopic analysis at 21 dai revealed that the resistant cultivar (JP) root structure remained largely unaffected, while the roots of the susceptible cultivar (83-1) exhibited significant tissue distortion and gall formation, underscoring the effectiveness of the resistance mechanisms. Comparative transcriptome analysis revealed substantial differences in the number and types of differentially expressed genes (DEGs) between the two cultivars, highlighting the key pathways involved in the resistance response. In the resistant cultivar (JP), a total of 9,433 DEGs were identified, with 4,211 up-regulated and 5,222 down-regulated. In contrast, the susceptible cultivar (83-1) exhibited 6,456 DEGs, with 2,781 up-regulated and 3,675 down-regulated. The resistant cultivar showed a pronounced activation of genes involved in hormone signaling, cell wall, secondary metabolism, redox state, and signaling process. Therefore, our speculation revolves around the potential resistant mechanism of this variety, which inhibits the proliferation of P. brassicae in the roots via secondary metabolites, cell wall, and ROS and also regulates physiological mechanisms mediated by plant hormones such as ABA to adapt to adverse environmental conditions such as water scarcity induced by the pathogen.ConclusionThis study unveils the intricate defense mechanisms potentially activated within Chinese cabbage when confronted with P. brassicae pathotype 11, offering valuable insights for breeding programs and the development of novel strategies for managing clubroot disease in Brassica crops. Furthermore, this study highlights the pivotal role of host-specific molecular defense mechanisms that underlie resistance to P. brassicae pathotype 11.